The role of breast MRI in the investigation of anti-Yo positive paraneoplastic cerebellar degeneration. (27th March 2012) - Real, Raquel; Oliveira, Ana; Nadais, Goreti; Loureiro, Joana; Garrett, Maria Carolina
Abstract : Paraneoplastic neurological syndromes are a group of rare and heterogeneous disorders complicating cancer through immune-mediated mechanisms. They typically arise before the diagnosis of malignancy, thus constituting its first clinical manifestation. A thorough search for the underlying tumour is necessary, as adequate tumour management is essential for both neurological prognosis and overall survival. The authors present the case of a 43 year-old woman who presented with a subacute cerebellar syndrome associated with the paraneoplastic anti-Yo antibody. Although paraneoplastic aetiology was immediately suspected, the diagnosis of the underlying tumour was not straightforward, as is often the case. This case report highlights the importance of directing tumour search for the most probable anatomic locations, according to patient demographics and risk factors as well as the type of onconeural antibodies present, and also the need to use the most sensitive diagnostic modalities appropriate for each target organ.